Team leadership and leadership roles - Kovačič, Helena (Metodološki zvezki, 2023)
Although leadership theory recognises the importance of leaders in a team, research has mostly focused on various personal characteristics of leaders or leadership style, while less attention has been paid to the social relationships in which leaders are embedded. We therefore examine both internal and external social ties of leaders with the aim of identifying variations in the network patterns of team leaders. We hypothesise that leaders' relationship patterns lead to different network structures, which in turn create differences in leadership roles. By examining the social networks of team leaders from Slovenian and Finnish organisations between 2009 and 2012, we empirically identify variations in leaders' social networks. The results suggest four distinct social structures within which team leaders perform their leadership roles. We have shown that leadership roles can be distinguished from teams and team leaders based on the characteristics of social networks.
Keywords: delovne skupine; družbena omrežja; socialna omrežja; socialni odnosi; vodenje